Estimation of the Monthly Albedo of the Earth’s Atmosphere over Sokoto, Nigeria - D. O. Akpootu; M. I. Iliyasu (Archives of Current Research International, 2017)
In this study, the shortwave solar energy balancing at the edge of the earth’s atmosphere was employed to estimate the variation of albedo for Sokoto, Nigeria (Latitude 13.02 N, Longitude 05.25 E and altitude 350.8 m above sea level). The measured meteorological parameters of monthly average daily global solar radiation, minimum and maximum temperature, relative humidity and rainfall during a period of thirty one years (1980-2010) were utilized in this study. The results show that the albedo depicts direct opposite relationship with the clearness index, an inverse relationship with the emitting earth’s surface temperature and direct relationship with the wavelength for the study area. The highest value of albedo simulated was in the month of August (0.4925) and the lowest in the month of November (0.3185). The emitting earth surface temperature for each month ranged between 235.2214 K in August and 253.2080 K in November, these values agrees closely to the standard emitting earth surface temperature (255.0000 K). The maximum emitting wavelength revealed that the radiation is longwave and are found within the infrared region of the electromagnetic spectrum. The albedo deduced from this study ranged from 0.3185 to 0.4925 which are consistent with the possible values of albedo of different surface covering the earth’s surface and agrees closely to the standard planetary albedo (0.3000). The estimated albedo is an important input parameter in evaluating solar energy collectors, radiative transfer in the atmosphere and studies dealing with thermal balance in the atmosphere. The variation of albedo with rainfall revealed that the highest and lowest albedo were observed in August and November where the region has its peak value in rainy season and onset of dry season. The highest albedo observed corresponds to the lowest solar radiation in August. The highest albedo observed in August corresponds to the minimum temperature attained in August when it decreases during the rainy season. The albedo and relative humidity depicts almost similar pattern and attained their highest values in August. The regression equations for estimating the albedo in relation to other parameters revealed that the clearness index and rainfall contributes most in albedo estimation for the study area under investigation and regions with similar climatic information.